Modification and testing of tractor operated KAU banana sucker uprooting machine - Naveen B V (Department of Farm Power Machinery and Energy, Kelappaji College of Agriucltural Engineering and Technology, 2017)
Banana (Musa paradisiaca) is a large perennials rhizome crops widely cultivated in India. These crops provide excellent opportunities in raising the income of farmers. Sucker is the planting material used for the cultivation of the banana. After the banan bunch harvesting, uprooting of mother corm and its suckers without damage is very essential for obtaining good quality planting material for banana cultivation and clearing of land is the main difficulty faced by banana farmers as less time is available between harvest and fresh planting of banana field. Uprooting the mother plant and suckers, clearing the land etc. are highly labour intensive in banana cultivation. As the entire state faces an acute shortage of labour, the development of suitable equipment for uprooting the banana clump in necessary. The present practice of uprooting was carried by digging out the soil-sucker composite by employing a labour using a sharp hatchets and spades the sword suckers should be dugout and separated from the mother plant. Uprooting takes lot of time and energy. In the University farms, one man labour uproots 15-20 clumps per day. At the present wage rate of Rs. 600 per man, an amount of Rs.48000 per acre is required for uprooting of banana clumps after harvest. The presently available mechanical banana uprooting device faces problems of excess fuel consumption, more time taken to uproot, high percentage of damage to suckers etc., hence a study was undertaken to modify the hydraulic operated banana sucker uprooting machine that was developed at KCAET, Tavanur. The machine was modified and field tested. . The physical and mechanical properties of banana rhizomes namely, size, shape and weight were found out using standard test procedures. Based on the effective root zone area and unit draft of the soil, the total draft force required to lift the clump was calculated. A john deer 5310 tractor 41.5 KW (55hp) was used as a prime mover. The machine (attachment) consists of a gib crane fitted with bucket with tyne at its lower end. The field performance of the machine was conducted for uprooting the banana soil-sucker in two types of soils, laterite soil at KCAET, Tavanur and clay soil at BRS Kannara. Trials were conducted to evaluate the performance of uprooter with 3 and 4 number of rectangular and triangular shape tynes. The uprooting was carried out for each of the treatment combinations. Performance analysis of the modified banana sucker uprooting machine was compared with respect to time, depth to penetration, percentage of damage of suckers and weight of soil -sucker clump separately with rectangular and triandular 3 and 4 number of tynes. The observations were separately recorded for clay soil and laterite soil. It was found that irrespective of the soil type, triangular shape with 4 number of tynes recorded lesser time for uprooting higher depth of penetration and lower percentage of damage while uprooting. Field efficiency of modified banana sucker uprooting was observed that the total time taken to uproot an area 0.0025 ha in clay soil was 1.8h. the field efficiency obtained was 75%. The total time taken to uproot an area 0.0025 ha in laterite soil was 1.5 h and field efficiency is 80%. Cost of uprooting by using uprooting machine is RS. 22,930 ha-1. the cost and time saved over manual uprooting was about 52.22% and 93.06%.